Challenges and Opportunities of Clinical Data Warehousing - Niklas GIESA; Anne Rike FLINT; Sedir MOHAMMED; Louis AGHA-MIR-SALIM; Sebastian Daniel BOIE; Fabian PRASSER; Felix BALZER (Applied Medical Informatics)
Clinical data warehousing (CDW) aims to provide an integrated database for secondary health analysis. We conducted a rapid review including 22 studies published between 2018 and 2022 that reported CWD implementation details in addition to individual experiences. Our results comprise technical details and reveal current opportunities and challenges of CDW. Many studies positively highlight standardized tools and models building on well-integrated clinical concepts. Enhanced tooling and data modeling were oftentimes hindered by bad data quality and organizational burdens. We call for enforcing synergies between clinical, technical, and organizational expertise to successfully roll out a CDW project.